4th International Conference on Manufacturing, Optimization, Industrial and Material Engineering 2016 (MOIME 2016). Issue 1 (May 2016) - Gaol, Ford Lumban; Webb, Jeff; Ding, Jun
Abstract : The 4th International Conference on Manufacturing, Optimization, Industrial and Material Engineering 2016 (MOIME 2016) was held in Bali Rani Hotel, Bali, Indonesia, from 19-20 March 2016. The MOIME 2016 conference aims to bring together researchers, engineers and scientists from around the world who work in the areas of interest. MOIME 2016 is focused on promoting interaction between the theoretical, experimental, and applied communities, so that a high level exchange is achieved in new and emerging areas within material engineering, industrial engineering and all areas that relate to optimization. We would like to express our sincere gratitude to all in the Technical Program Committee who have reviewed the papers and developed a very interesting conference program, as well as to the invited and plenary speakers. This year, we received 117 papers and after rigorous review, 25 papers were accepted. The participants came from seven countries and there were six parallel sessions and three keynote speakers. It is an honour to present this volume of IOP Conference Series: Materials Science and Engineering (MSE) and we deeply thank the authors for their enthusiastic and high-grade contributions. Finally, we would like to thank the conference chairmen, the members of the steering committee, the organizing committee, the organizing secretariat and the financial support from the conference sponsors that allowed MOIME 2016 to be a success. the Editors of the MOIME 2016 Proceedings Dr. Ford Lumban Gaol, Jeff Webb, Ph.D and Prof. Jun DING, Ph.D